The Antecedents of Customer Loyalty: A Study for Life Insurance in Vietnam - Thi Huong Mai (International Journal of Small and Medium Enterprises and Business Sustainability, 2023)
In the context of increasingly fierce competition, retaining customers as well as promoting repurchase behavior is the foundation for companies to create and maintain sustainable business performance. Therefore, customer loyalty is considered an essential goal for the existence and development of every business. Building a loyal customer base has become a major goal in marketing programs (Karyose et al., 2017) and is considered an important goal for the survival and growth of a business. It is also an important basis for developing a sustainable competitive advantage, where the life insurance industry is no exception (Ruefenacht, 2018). Although the existing service marketing literature has extensively studied customer loyalty and revealed several customer loyalty premises, such as the discovery of trust (Van Tonder, 2016), customer value (Ishaq, 2012), service value (Li and Green, 2011), and most notably, satisfaction (Akbar and Parvez, 2009). However, studies that specifically address such loyalty in relation to the features of the insurance sector are scarce (Guillen et al., 2012). This study aims to explore the relationship between customer satisfaction and customer loyalty in the life insurance sector with the mediating variables of trust. The research results are the premise to propose solutions to promote customer loyalty as well as increase the intention and behavior of buying life insurance in Vietnam today.